2005
DOI: 10.1002/chin.200518296
|View full text |Cite
|
Sign up to set email alerts
|

Selected Drugs in Solid Matrices: A Review of Environmental Determination, Occurrence and Properties of Principal Substances

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 1 publication
0
15
1
Order By: Relevance
“…For some antibiotics, especially hydrophobic antibiotics, with their limited mobility and low biodegradation in the sludge, they are prone to adsorb onto sewage sludge and more stable than those in wastewater (Baquero et al, 2008;Cruz Moreno-Bondi et al, 2009;Zhou et al, 2009). Several studies have reported that many antibiotics in wastewater were considerably eliminated by sorption and transported to sewage sludge during sewage treatment (Batt et al, 2007;Beausse, 2004;Escher et al, 2011;Hörsing et al, 2011), indicating that sludge can serve as an important reservoir of antibiotics. Therefore, concentrations of antibiotics in sewage sludge can give an important indication on their pollution levels to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…For some antibiotics, especially hydrophobic antibiotics, with their limited mobility and low biodegradation in the sludge, they are prone to adsorb onto sewage sludge and more stable than those in wastewater (Baquero et al, 2008;Cruz Moreno-Bondi et al, 2009;Zhou et al, 2009). Several studies have reported that many antibiotics in wastewater were considerably eliminated by sorption and transported to sewage sludge during sewage treatment (Batt et al, 2007;Beausse, 2004;Escher et al, 2011;Hörsing et al, 2011), indicating that sludge can serve as an important reservoir of antibiotics. Therefore, concentrations of antibiotics in sewage sludge can give an important indication on their pollution levels to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic toxicity data for algae and invertebrates have become more available in recent years, although they are usually obtained from aqueous-exposure experiments [6] rather than from field studies. Although pharmaceuticals are often moderately lipophilic [7], few studies have examined their potential impact on benthic communities and sediment organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceuticals are classified as the socalled "microcontaminants", which have been causing significant concern within the environmental area during past years. (Beausse 2004;Gómez et al ,2006) The most pharmaceuticlas are not completely removed in the wastewater treatment plant (Beausse, 2004;Gómez et al, 2006;Ramirez et al, 2007). They are partially eliminated by s o r p t i o n t o w a s t e w a t e r s l u d g e o r b y b i o d egradadion.…”
Section: Pharmaceuticalsmentioning
confidence: 99%